Upaya Pengentasan Stunting di Nagori Bahkisat Kec.Tanah Jawa Bersama KKN MANDIRI 225 Stunting UINSU - Maisyar, Ahmad; Siregar, Yusherdiansyah; Sari, Dewi Ratna; Syahara, Falya; Saripuddin, Muhammad (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Stunting is a serious problem faced by Indonesia, especially in remote villages. So, the purpose of this research is to find out the stunting alleviation efforts carried out in Nagori Bahkisat Kec. Javanese land. This research was conducted by conducting field observations, and was written using a descriptive qualitative research method. Researchers collected data by means of interviews, field observations, documentation, and literature studies to strengthen the data obtained. The results of this study are stunting in simalungun district is not too high, because it does not reach tens of children who suffer from stunting. Efforts are being made to continue to reduce the stunting rate in this area by conducting socialization on stunting prevention for children, and the people in Nagori Bahkisat regularly check at the Posyandu. Stunting is a serious problem faced by Indonesia, especially in remote villages. So, the purpose of this research is to find out the stunting alleviation efforts carried out in Nagori Bahkisat Kec. Javanese land. This research was conducted by conducting field observations, and was written using a descriptive qualitative research method. Researchers collected data by means of interviews, field observations, documentation, and literature studies to strengthen the data obtained. The results of this study are stunting in simalungun district is not too high, because it does not reach tens of children who suffer from stunting. Efforts are being made to continue to reduce the stunting rate in this area by conducting socialization on stunting prevention for children, and the people in Nagori Bahkisat regularly check at the Posyandu. Stunting is a serious problem faced by Indonesia, especially in remote villages. So, the purpose of this research is to find out the stunting alleviation efforts carried out in Nagori Bahkisat Kec. Javanese land. This research was conducted by conducting field observations, and was written using a descriptive qualitative research method. Researchers collected data by means of interviews, field observations, documentation, and literature studies to strengthen the data obtained. The results of this study are stunting in simalungun district is not too high, because it does not reach tens of children who suffer from stunting. Efforts are being made to continue to reduce the stunting rate in this area by conducting socialization on stunting prevention for children, and the people in Nagori Bahkisat regularly check at the Posyandu.